TGF-β2 Reduces the Cell-Mediated Immunogenicity of Equine MHC-Mismatched Bone Marrow-Derived Mesenchymal Stem Cells Without Altering Immunomodulatory Properties - Berglund, Alix K.; Long, Julie M.; Robertson, James B.; Schnabel, Lauren V. (Frontiers in Cell and Developmental Biology, 2021)
Allogeneic mesenchymal stem cells (MSCs) are a promising cell therapy for treating numerous diseases, but MHC-mismatched MSCs can be rejected by the recipient’s immune system. Pre-treating MSCs with TGF-β2 to downregulate surface expression of MHC molecules may enhance the ability of allogeneic MSCs to evade immune responses. We used lymphocyte proliferation assays and ELISAs to analyze the immunomodulatory potential of TGF-β2-treated equine bone marrow-derived MSCs. T cell activation and cytotoxicity assays were then used to measure the in vitro cell-mediated immunogenicity. Similar to untreated MSCs, TGF-β2-treated MSCs inhibited T cell proliferation and did not stimulate MHC-mismatched T cells to proliferate. Additionally, similar quantities of PGE2 and TGF-β1 were detected in assays with untreated and TGF-β2-treated MSCs supporting that TGF-β2-treated MSCs retain their strong immunomodulatory properties in vitro. Compared to untreated MSCs, TGF-β2-treated MSCs induced less T cell activation and had reduced cell-mediated cytotoxicity in vitro. These results indicate that treating MSCs with TGF-β2 is a promising strategy to reduce the cell-mediated immunogenicity of MHC-mismatched MSCs and facilitate allogeneic MSC therapy.